EFFECT OF CORPORATE GOVERNANCE ON INTELLECTUAL CAPITAL DISCLOSURE - Hesniati, Hesniati (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Disclosure of intellectual capital is essential in providing information about the company's intellectual assets in knowledge economy era. The purpose of this study is to acquire empirical evidence of how corporate governance influences the disclosure of intellectual capital of Indonesian listed companies in Kompas 100 Index. The sample consisted of 48 listed companies that had been sorted and tested using multiple linear regression methods. The outcome of the study showed that independent commissioner composition had no effect on intellectual capital disclosure. Board size, audit meeting, and audit committee have a significant positive effect on intellectual capital disclosure.